Study on solid waste generation and composition at balakong city, selangor - Abu Samah, Mohd Armi; Yunus, Kamaruzzaman; Mohd. Aris, Mohd Shukri (2016)
Increasing of solid waste is one of the most crucial environmental problems in Malaysia. Improper management of solid waste will cause many problems. Increasing solid waste, no segregation from the source and lack of knowledge and awareness about recycling has more worsened to the problem. Most of Malaysian such Balakong City Selangor generally the waste is mixed which means there is organic and inorganic waste. Organic waste can be used as composting materials meanwhile inorganic waste can be used and send for recovery and recycle. Knowledge of solid waste generation and composition is necessary for an accurate decision making in the best management strategy of municipal solid waste. This study has shown waste generation and composition at Balakong City Selangor. From the waste generation and composition, a proper waste management system had introduced to treat solid waste more efficiently. Solid waste measurement that has been applied is using a direct method which is direct sampling or weighting from the solid waste collected. It mainly consists of three main stages which is weighing, recording and analysing the data. The data collection was conducted for a certain period and the weighing process was done every day. The result from this study was found that the total waste generated for a month in residential, shopping and industrial area in Balakong City was approximately 31,536.1 Kg. Beside that for the total of waste composition are made up of with the organic waste (15,158.8 Kg), paper (9,313.2 Kg), plastic (5,263.00 Kg), glass (599.8 Kg), metal (365.2 Kg) and others (836.14 Kg).